2002
DOI: 10.1038/sj.ejcn.1601349
|View full text |Cite
|
Sign up to set email alerts
|

Meat consumption and cancer of the large bowel

Abstract: studies relating (red) meat consumption and colorectal cancer have been published or found by search. These are collected here.Thirty adequate case -control studies have been published up to 1999 (from 16 different countries). Twenty of them found no significant association of (red) meat with colorectal cancer. Of the remaining 10 studies reporting an association, some obtained statistical significance only in rectal or colon cancers, another only in men, not women, or found a stronger association with pasta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…1 27 Red meat consumption was considered a probable risk factor for colorectal cancer in the 1997 WCRF report (1). Since then, several other expert groups have reassessed the epidemiological data, including those published after the WCRF report (18)(19)(20)(21)(22)(23)(24)(25). Similar to our data, the results of many of these studies did not reach statistically significant levels.…”
Section: Downloaded By [North West University] At 12:31 20 December 2014supporting
confidence: 63%
“…1 27 Red meat consumption was considered a probable risk factor for colorectal cancer in the 1997 WCRF report (1). Since then, several other expert groups have reassessed the epidemiological data, including those published after the WCRF report (18)(19)(20)(21)(22)(23)(24)(25). Similar to our data, the results of many of these studies did not reach statistically significant levels.…”
Section: Downloaded By [North West University] At 12:31 20 December 2014supporting
confidence: 63%
“…Debates about the potential role of red meat consumption in colorectal carcinogenesis have been especially pronounced [World Cancer Research Fund (WCRF)/American Institute for Cancer Research (AICR), 1997; Truswell, 2002;Gonzalez and Riboli, 2006;Baghurst, 2007; World Cancer Research Fund (WCRF)/American Institute for Cancer Research, 2007;Boyle et al, 2008;Huxley et al, 2009;Truswell, 2009;McAfee et al, 2010]. For example, the World Cancer Research Fund (WCRF) in collaboration with the American Institute for Cancer Research (AICR) judged that red meat is a convincing cause of CRC in a report published in 2007 [World Cancer Research Fund (WCRF)/ American Institute for Cancer Research, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Epidemiologic studies have shown that not only prostate cancer but also colorectal carcinoma (CRC) has positive correlation with consumption of red and processed meat. [5][6][7][8] Recently, AMACR has been demonstrated to be overexpressed in primary and metastatic prostate cancers, and it has been used as an important diagnostic marker in the prostate to distinguish normal glands from prostate cancer. [9][10][11][12] However, in contrast to prostate cancer, there has been limited investigation of this enzyme in CRC.…”
mentioning
confidence: 99%